Determinants of Compliance with the Implementation of the Covid-19 Health Protocol for High School Students in Kampa District Kampar District - nur helmi; Dedi Afandi; Doni Jepisah; Hetty Ismainar; Novita Rany (LPPM Hang Tuah Pekanbaru, 2022)
In 2021, countries in the world have tested positive for COVID-19 with a total case of more than 184,572,371 million people. One of the countries affected by COVID-19 is Indonesia. Covid-19 first entered Indonesia in March 2020, until July 8, 2021, there were 2,417,788 cases of covid-19 in Indonesia. Health protocol compliance is defined as individual behavior by healthy behavior regulations during a pandemic that has been set by the government The purpose of this study was to determine the determinants of compliance with the implementation of the COVID-19 health protocol in high school students in the Kampa District in 2021. This study used an observational analytical quantitative approach with an Analytical Cross-Sectional Study design or an analytical cross-sectional study design that aims to determine the relationship between factors certain diseases or health problems. This research was conducted in July 2021. The study used univariate, bivariate, and multivariate analysis. Respondents in this study amounted to 286 respondents from all high school students in Kampa District. The results showed that p-value < 0.05 were among others the teacher's role variable (p = 0.000) with POR = 6.093, means variable (p = 0.000) with POR = 4.487, perception variable (p = 0.040) with POR = 1.897 and The unrelated variables were unrelated, attitude (p=0,289) with POR = 1,386, source of information (p=0,257) with POR = 1,450, parental support (p=0,074) with POR 1,986 and knowledge (p-0,053) with POR = 0.208. The determinants of compliance with the implementation of the COVID-19 health protocol in high school students are the role of teachers, facilities, and perceptions. The need to improve health promotion with various efforts, such as utilizing social media trends as well as print and electronic media, making it easier for students to understand more about compliance with the implementation of the 2019 coronavirus disease health protocol.